2021
DOI: 10.1007/s11548-021-02393-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual 3D-printed fixation masks for radiotherapy: first clinical experiences

Abstract: Purpose To show the feasibility of 3D-printed fixation masks for whole brain radiation therapy in a clinical setting and perform a first comparison to an established thermoplastic mask system. Methods Six patients were irradiated with whole brain radiotherapy using individually 3D-printed masks. Daily image guidance and position correction were performed prior to each irradiation fraction. The vectors of the daily position correction were compared to two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…However, to date there are very few reports on the use of this method in the clinical medicine, especially in radiotherapy. Mattke et al [16] explored the feasibility of 3D-printed fixation masks for whole brain radiation therapy in a clinical setting and performed a first comparison to an established thermoplastic mask system. Six patients were irradiated with whole brain radiotherapy using individually 3D-printed masks.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there are very few reports on the use of this method in the clinical medicine, especially in radiotherapy. Mattke et al [16] explored the feasibility of 3D-printed fixation masks for whole brain radiation therapy in a clinical setting and performed a first comparison to an established thermoplastic mask system. Six patients were irradiated with whole brain radiotherapy using individually 3D-printed masks.…”
Section: Discussionmentioning
confidence: 99%
“…M. Mattke et al. ( 8 ) also found the fixation accuracy of 3D-printed cephalic masks is lower than that of conventional cephalic fixation. Nonetheless, the fixation accuracy of 3D-printed cephalic masks is within the allowable error range.…”
Section: Introductionmentioning
confidence: 99%
“…Ghazal Shafai-Erfani et al (7) found systematic errors of 1.1, 2.0, and 2.3 mm in the left-right, head-foot, and anterior-posterior directions, respectively, for the headrest plus mask fixation technique. M. Mattke et al (8) found mean positional errors of 0.9, 2.28, and 1.9 mm in the left-right, head-foot, and anteriorposterior directions, respectively, for patients undergoing wholebrain radiotherapy using headrest plus mask fixation. These findings indicate that the accuracy of standard headrest and mask fixation should be improved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations